Spectral Radiative Properties of a Liquid n-Octane Droplet in the Midinfrared Region - Liang Zhao; Chaoyu Jing; Yu Jin; Jiangping Chen; Ke Yin; Sujun Yang; Bingqing Liu; Xiao Han; Jianyu Tan (Journal of Spectroscopy)
The optical constants of a liquid hydrocarbon such as liquid n-octane are basic material properties that may be used to evaluate their thermal radiation transfer capabilities. In this study, the ellipsometry method was used to measure the optical constants of liquid n-octane in the midinfrared wavelength range of 2.0–16.0 μm at temperatures of 20, 50, and 80°C. Experimental analyses indicate the significant effect of temperature on the refractive index, although it has little effect on the absorption index. With increasing temperature, the refractive index shows a linear decrease, and reduced density leads to weaker absorption intensities. The radiative properties of n-octane droplets, including the absorption and scattering efficiency factors of single droplets with droplet radii r = 10, 20, 50, and 100 μm and the absorption and scattering coefficients in a droplets-air system of droplet volume fractions fv = 2%, 3%, and 4%, were calculated using Mie theory. The numerical results indicate that, with increasing temperature, the absorption efficiency factor slightly decreases, and the variation trend of the scattering efficiency factor is more complicated. With increasing droplet radius, the absorption efficiency factor increases within the studied wavelength range, except for certain absorption peaks, but the scattering efficiency factor tends to decrease. While the absorption is greater, the scattering is weaker for a given droplet radius. With an increasing volume fraction of n-octane droplets, the absorption and scattering coefficients increase linearly within the studied wavelength range.